Students of Autonomous Learning Using Mobile Assisted Language Learning (MALL) at Senior High School - Syamsir Syamsir; Bahrun Amin; Erwin Akib; Radiah Hamid (Institut Agama Islam Negeri Palopo, 2022)
This research aimed to improve the students’ listening in autonomous learning using Mobile Assisted Language Learning (MALL), this research was conducted in SMAN 18 Bulukumba. The data had been counted by the researcher, then the researcher consider about the implementation of autonomous learning using MALL.In conducted this research, the researcher gave the students autonomous learning and the students work. The data were got using the test for the students, then the data counted by researcher by using Classroom Action Research method of data collection technique, and also through documentation with 32 students in the classroom.The Results of this research showed that autonomous learning using Mobile Assisted Language Learning (MALL) can improve the students’ listening, especially in Respond and Understand of their mobile phone by using several applications podcasts; it proven by the results of the test, where the students’ achievement in listening respond and understand was shown by the students’ scores in D-test (50 and 55.7), Cycle I (60.3 and 60), and Cycle II (81.1 and 71.). Hopefully, the result of this research is able to be replicated by SMAN teachers and students in solving similar problems faced in autonomous learning using Mobile Assisted Language Learning (MALL).